Răspuns :
Pai daca a+b=66
a-b=10,4
=>2a+b-b=66+10,4 <=> a=38,2 => b=27,8
Dar astea nu verifica in prima relatie . Inseamna ca una din cele 3 relatii este gresita
a-b=10,4
=>2a+b-b=66+10,4 <=> a=38,2 => b=27,8
Dar astea nu verifica in prima relatie . Inseamna ca una din cele 3 relatii este gresita
a)...
a = 2,3*b => a+b = 66 ⇔ 2,3b+b=66 ; b=66:3,3=20
↓
a=2,3*20=46
b)...
a = 2,3b => a-b = 10,4 ⇔ 2,3b-b=10,4; b=10,4:1,3=8
↓
a= 2,3*8=18,4
a = 2,3*b => a+b = 66 ⇔ 2,3b+b=66 ; b=66:3,3=20
↓
a=2,3*20=46
b)...
a = 2,3b => a-b = 10,4 ⇔ 2,3b-b=10,4; b=10,4:1,3=8
↓
a= 2,3*8=18,4